DINAMIKA PEMBELAJARAN IPS di MTS AL-HUDA PADA KURIKULUM MERDEKA BELAJAR - Wafiyatu Maslahah; Lailatul Rofiah; Tika Lailatul Nisa (LPSDI Bina Patria, 2024)
This research is motivated by the researcher's interest in photographing the social studies learning process in a private school in the city of Malang. The focus of this research interest is that MTs Al-Huda is still a relatively new school in the city of Malang and students are only devoted to girls. Thus the researcher is interested in taking research with the title Analysis of Social Studies Learning in the Independent Learning Curriculum at MTs Al-Huda. The purpose of this study was to examine the social studies learning process with the help of the independent learning curriculum in class VII starting from the planning, implementation to the evaluation stage used. This type of research is phenomenology with a qualitative approach. Data collection through observation, in-depth interviews and documentation. The results of this research explore that social studies learning using the independent learning curriculum at MTs Al-Huda has been going quite well. The teacher prepares lesson plans before teaching. Implementation of learning carried out by the teacher in accordance with the plan that has been designed. After the learning process takes place, the teacher always evaluates students.